Dampak Pandemi Covid-19 Terhadap Penurunan Pendapatan Masyarakat di Bukit Lawang Menurut Ekonomi Islam - Maryam Batubara; Muhammad Arif; Myrna Dwi Tania (ITB AAS INDONESIA Surakarta, 2022)
The tourism sector is one of the biggest foreign exchange earners for Indonesia, it can be seen how the government focuses on the development of tourism throughout the country. Bukit Lawang is a small village located 90 kilometers northwest of Medan, North Sumatra. The village, which is part of the Bahorok District, is famous for its swift and clear river currents and is a place for observing wild Sumatran orangutans in the protected forest area of Gunung Leuser National Park. This type of research is qualitative with a phenomenological approach with interview data collection methods to informants. The research location is in Bukit Lawang Village, Bahorok District. It was found that the impact of the Covid-19 pandemic on the income of the community around the Bukit Lawang tourist attraction has decreased significantly. The income of people working in the tourism sector who are entrepreneurship both in the business of goods and services around the Bukit Lawang tourist attraction, which was initially classified as stable, decreased by 70% to 100%. lazy informants in looking for other alternatives. Awareness of responsibility as the head of the family and awareness of religious orders is very minimal seen in the lack of prayer, fasting and paying zakat.